Psychotria hoffmannseggiana: uma nova espécie de planta tóxica para bovinos - Heloísa de Paula Pedroza (2015)
Several plants species in Brazil produce poisoning in cattle known as sudden death. The toxic compound of most of these species has been confirmed as monofluoroacetate (MFA), a compound which promotes blocking of the citric acid cycle. In the Brazilian state of Minas Gerais, a species of plant known as erva de rato has been implicated as responsible for several outbreaks of poisoning in cattle, but this species is different from Palicourea species described as toxic. Thus, this study aimed to identify this species, report natural poisoning outbreak, determine whether the toxic principle is the MFA and compare techniques for the identification of this compound. The plant was identified as Psychotria hoffmannseggiana. The poisoning outbreaks have been reported only in cattle and are similar to those observed with Palicourea marcgravii. The toxic principle has been confirmed as the MFA in plant samples collected at the local of outbreak. On the other hand, the cultivated plant showed no detectable levels of MFA, which indicates that the composition of the soil and/or microorganisms associated with plant roots are decisive factors for the production of this toxic compound. The determination of the MFA by thin layer chromatography (TLC) was considered of low sensitivity and specificity. The liquid chromatography technique (HPLC) with UV detector and separation of C-610H column for organic acids (Supelcogel) was quite effective, with best results after clean up with activated charcoal. Even after drying and storage for 45 days at room temperature, MFA levels remained stable in the plant. Thus, it was found that Psychotria hoffmannseggiana is a toxic plant containing MFA.